Function value of basement membrane-related genes in odontogenic keratocyst by bioinformatics analysis - Yi, Jing-Rui; Zhong, Nian-Nian; Liu, Xuan-Hao; Zhu, Zheng-Rui; Zhang, Yi-Jia-Ning; Liu, Bing; Man, Qi-Wen (Frontiers in Oncology, 2025)
BackgroundOdontogenic keratocyst (OKC) is an aggressive jaw lesion characterized by high recurrence rates. Disruption of the basement membrane (BM) may contribute to its pathogenesis, through the underlying molecular mechanisms remain incompletely understood.MethodsTranscriptomic data from 12 non-syndromic OKC and 4 normal oral mucosa (NOM) samples (GSE38494) were analyzed to identify differentially expressed BM-related genes (BM DEGs). Bioinformatics approaches included differential expression analysis, functional enrichment (Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, Gene Set Enrichment Analysis), protein-protein interaction (PPI) network construction, immune infiltration assessment, and validation via single-cell RNA-seq (scRNA-seq; GSE176351). Key findings were confirmed immunohistochemistry and by immunofluorescence in clinical specimens.ResultsA total of 65 BM DEGs were identified, with secreted protein acidic and cysteine rich (SPARC) being the most significantly upregulated gene (P < 0.01). PPI and correlation analyses established SPARC as a hub gene, showing significant correlation with recognized OKC markers (PTCH1, GLI1, GLI2, KRT19; P < 0.05). ScRNA-seq localized elevated SPARC expression predominantly to stromal fibroblasts. Immunohistochemistry and immunofluorescence confirmed significantly higher stromal SPARC expression in OKC versus NOM (P = 0.001). SPARC levels correlated with altered immune infiltration profiles, showing positive association with effector memory CD4+ T cells and negative association with memory B cells. Transcription factor and microRNA regulatory networks for SPARC were delineated.ConclusionsThis study establishes dysregulation f BMGs—particularly stromal fibroblast-specific SPARC overexpression—as a contributor to OKC pathogenesis. SPARC interacts with key OKC pathways (Hedgehog, NOTCH) and modulates the immune microenvironment. These findings provide foundational insights into OKC aggressiveness and propose SPARC as a potential therapeutic target.